(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Women’s reproductive health is not only a significant issue for women, but also an essential determinant shaping the entire health scenario of women. It starts with their birth or even from the moment of conception and continues till death. Reproductive health of a woman is determined by a numerous complex biological, social, behavioral, cultural, and physical factors. These socio-cultural factors have significant effect on total fertility rate, contraceptive prevalence, menstrual behavior, family planning, maternal mortality, age at marriage, perception of an ideal number of children, etc. which are major indicators of Reproductive Health. To focus on these issues the present study was conducted to analyze the effect of the socio cultural factors on reproductive health of women. The study was conducted in 6 wards of Haldwani city, of Nainital district Uttarakhand (150 female respondents of reproductive age group) by using exploratory cum descriptive research design using SPSS 26.0 version for analysis. Findings of the study reflect that socio cultural factors like menstrual taboos, fertility rate is significantly associated with the religious factor and exerts huge impact on reproductive health outcomes of women. Whereas the preference of family type during pregnancy period is not significantly associated with religion as women of both the religion found comfortable to reside in joint family as it provide them huge support to overcome their pre and post pregnancy complications.